2021
DOI: 10.3390/polym14010014
|View full text |Cite
|
Sign up to set email alerts
|

Color Stability, Chemico-Physical and Optical Features of the Most Common PETG and PU Based Orthodontic Aligners for Clear Aligner Therapy

Abstract: It is difficult to find research papers collecting comparative results about characterization studies of clear aligners. Therefore, the aim of this paper is to provide the first comparative analysis of most commercial clear aligners, in terms of their stability towards intra-oral staining agents, their physicochemical and optical properties, as well as their water absorption behavior. Five types of aligners, characterized by different techniques, are considered: Erkodur, Essix Plastic, Ghost Aligner, Zendura, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 27 publications
(60 reference statements)
2
17
0
3
Order By: Relevance
“…Peaks observed at 791, 1146, and 1588 cm −1 confirmed the presence of PSF in the polymer system. These peaks were attributed to asymmetric CSC, COC and aromatic chain vibrations of PSF, respectively 50,51 . Presence of h‐BN in polymer host system was confirmed by peak appeared at 1378 cm −1 correlated to the E 2 g phonon mode 52,53 .…”
Section: Resultsmentioning
confidence: 85%
“…Peaks observed at 791, 1146, and 1588 cm −1 confirmed the presence of PSF in the polymer system. These peaks were attributed to asymmetric CSC, COC and aromatic chain vibrations of PSF, respectively 50,51 . Presence of h‐BN in polymer host system was confirmed by peak appeared at 1378 cm −1 correlated to the E 2 g phonon mode 52,53 .…”
Section: Resultsmentioning
confidence: 85%
“…Since clear retainer material interactions with the oral environment can occur, resulting in plaque and calculus buildup along with bacteria buildup and retention, clear retainers must be maintained to mitigate loss of their light transmittance and maintain material integrity [ 5 , 6 , 7 , 8 , 21 ]. Color stability can also be affected by ultraviolet radiation, mouthwash, and various beverages [ 5 , 6 , 7 , 8 , 22 ]. Additionally, in the United States, 50% of Americans over 18 years old drink coffee, and coffee drinkers consume an average of three cups of coffee per day [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most popular thermoplastic materials currently used for the production of clear aligners are polyester‐based: polyethylene terephthalate glycol modified (PET‐G); and polyester urethane [13]. These materials present a very low crystalline order [14], which is inversely related to the degree of transparency [15]. The PET‐G‐based aligners have been demonstrated to have lower light absorption values than the polyester urethane aligners, probably owing to differences in the chemical composition or the different thermoforming procedures applied [14].…”
Section: Introductionmentioning
confidence: 99%
“…These materials present a very low crystalline order [14], which is inversely related to the degree of transparency [15]. The PET‐G‐based aligners have been demonstrated to have lower light absorption values than the polyester urethane aligners, probably owing to differences in the chemical composition or the different thermoforming procedures applied [14]. Moreover, it has been shown that rigid and chemically inert polyurethane aligners of 0.75 mm thickness have significantly higher transmittance and lower absorbance than either PET‐G‐based aligners of 0.8 mm thickness or polyester urethane aligners of 0.75 mm thickness [16].…”
Section: Introductionmentioning
confidence: 99%